2021
DOI: 10.15376/biores.16.2.2249-2263
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of briquettes fuel using Pinus spp. sawdust from five regions of Mexico

Abstract: This research characterized briquettes made with Pinus spp. sawdust without the use of additives. For this purpose, 19 samples of sawdust from different wood industries located in five states of the Mexican Republic were used. The densification process was carried out in a vertical hydraulic piston laboratory briquette machine. The briquettes were made with 40 g of sawdust, at 50 °C, 20 kPa and pressing for 5 min. The results obtained varied as follows: moisture content (4.1% to 7.2%), density (813.9 to 1,014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
(37 reference statements)
5
8
0
Order By: Relevance
“…On the other hand, Pinus pseudostrobus, P. leiophylla, P. hartwegii, P. lawsonii, and P. devoniana were positioned within the range (0.13% to 0.23%) for bioenergy use reported by Pintor-Ibarra et al (2017). All conifers in this study were within the range (0.1% to 1.1%) reported for pine sawdust (Ramírez-Ramírez et al 2021). In general, ash content in conifers is lower than in broadleaved hardwoods, which coincides with the study by Gutiérrez-Acosta et al (2021).…”
Section: Proximal Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, Pinus pseudostrobus, P. leiophylla, P. hartwegii, P. lawsonii, and P. devoniana were positioned within the range (0.13% to 0.23%) for bioenergy use reported by Pintor-Ibarra et al (2017). All conifers in this study were within the range (0.1% to 1.1%) reported for pine sawdust (Ramírez-Ramírez et al 2021). In general, ash content in conifers is lower than in broadleaved hardwoods, which coincides with the study by Gutiérrez-Acosta et al (2021).…”
Section: Proximal Analysissupporting
confidence: 88%
“…For fixed carbon, it is considered that the higher it is, the better the fuel quality is. In addition, fixed carbon is an important generator of heat during combustion (Kongprasert et al 2019); different studies agree that the value of fixed carbon in biomass fuels in the form of firewood or densified, does not exceed 30% (Uceda 1984, Vassilev et al 2010, Ruiz-Aquino et al 2019, Ramírez-Ramírez et al 2021. In the HHV, lignin (25.58 MJ•kg -1 ) was taken as the maximum value because, in general, the HHV of biomass fuels increases with lignin content and is highly correlated (Demirbaş 2001(Demirbaş , 2002(Demirbaş , 2003.…”
Section: Fuel Numbermentioning
confidence: 99%
“…These values were found to be comparable to those reported for Eucalyptus grandis × Eucalyptus urophylla, which were 87.95%, 11.59%, and 0.46%, respectively [27]. Regarding the higher and lower calorific values, they fell within the ranges of 19.43 to 20.28 and 18.13 to 18.84 kJ/kg, respectively, resembling those typically observed for hardwood [28], although lower than those found in softwoods [29]. The relatively lower calorific value of hardwoods can be attributed to the structure of lignin, where the presence of syringyl units increases the number of ether bonds, leading to a less condensed structure [29,30].…”
Section: Chemical Characterization Of Woodsupporting
confidence: 85%
“…Regarding the higher and lower calorific values, they fell within the ranges of 19.43 to 20.28 and 18.13 to 18.84 kJ/kg, respectively, resembling those typically observed for hardwood [28], although lower than those found in softwoods [29]. The relatively lower calorific value of hardwoods can be attributed to the structure of lignin, where the presence of syringyl units increases the number of ether bonds, leading to a less condensed structure [29,30]. Conversely, the higher resin content in softwoods contributes to their higher calorific value [31].…”
Section: Chemical Characterization Of Woodsupporting
confidence: 76%
“…The volumetric swelling of briquettes from all mixtures was found to be below the range of 15 to 20% recommended by Maradiaga et al [29]. Despite the relatively high humidity to which the briquettes were subjected in the conditioned room, briquettes with lower percentages of volumetric swelling than reported by Ramírez-Ramírez et al [43] were found, and also maintained a firm consistency. Swelling values lower than 3% were observed with high proportions of large particles mixed with any or smaller proportions of medium and small particles, such as in the T10 (33:0:67), T1 (100:0:0), T0 (12:71:17), T9 (33:67:0), T4 (33:33:0), T6 (67:0:33), and T5 (67:33:0) mixtures.…”
Section: Volumetric Swellingmentioning
confidence: 49%